Silent infarct is a risk factor for infarct recurrence in adults with sickle cell anemia. (21st August 2018) - Jordan, Lori C.; Kassim, Adetola A.; Donahue, Manus J.; Juttukonda, Meher R.; Pruthi, Sumit; Davis, Larry T.; Rodeghier, Mark; Lee, Chelsea A.; Patel, Niral J.; DeBaun, Michael R.
Abstract : Objective: Because of the high prevalence of silent cerebral infarcts (SCIs) in adults with sickle cell anemia (SCA) and lack of information to guide treatment strategies, we evaluated the risk of recurrent SCIs and overt stroke in adults with SCA with preexisting SCI. Methods: This observational study included adults with SCA (HbSS or Sβ 0 thalassemia) aged 18 to 40 years. Participants received 3-tesla brain MRI and a detailed neurologic examination. Time-to-event analysis assessed those with or without baseline SCI and with new or progressive infarcts. The incidence rate of new events was compared by log-rank test. Univariable Cox regression assessed the association of SCI with infarct progression. Results: Among adults with SCA with 2 MRIs and at least 6 months between MRIs (n = 54, mean interval = 2.5 years), 43% had SCI at baseline. Of participants with baseline SCI, 30% had new or progressive SCI over 2.5 years compared to 6% with no SCI at baseline; no participant had an overt stroke. New SCIs at follow-up were present in 12.9 per 100 patient-years with existing SCI compared with 2.4 per 100 patient-years without prior SCI (log-rank test, p = 0.021). No statistically significant differences were seen among those with or without baseline SCI in use of hydroxyurea therapy, hydroxyurea dose, or other stroke risk factors. The presence of SCI was associated with increased hazard of a new or progressive infarct (hazard ratio 5.27, 95% confidence interval 1.09–25.51, p = 0.039). Conclusions: Silent infarcts in adults with SCA are common and are a significant risk factor for future silent infarcts.